Experimental Characterization of a Commercial Photovoltaic Thermal (PVT) Hybrid Panel Under Variable Hydrodynamic and Thermal Conditions - Jorge Aguilar; Wilson Pavon; Zahir Dehouche (Energies, 2025)
Photovoltaic thermal (PVT) hybrid systems offer a promising approach to maximizing solar energy utilization by combining electricity generation with thermal energy recovery. This study presents an experimental evaluation of a commercially available PVT panel, focusing on its thermal performance under varying inlet temperatures and flow rates. The work addresses a gap in the literature regarding the real-world behavior of integrated systems, particularly in residential settings where space constraints and energy efficiency are crucial. Experimental tests were conducted at three mass flow rates and five inlet water temperatures, demonstrating that lower inlet temperatures and higher flow rates consistently improve thermal efficiency. The best-performing condition was achieved at 0.012 kg/s and 10 °C. These findings deepen our understanding of the panel’s thermal behavior and confirm its suitability for practical applications. The experimental platform developed in this study also enables standardized PVT testing under controlled conditions, supporting consistent evaluation across different settings and contributing to global optimization efforts for hybrid solar technologies.